3D truss structures with coreless 3D filament winding technology. (June 2019) - Minsch, Niklas; Müller, Matthias; Gereke, Thomas; Nocke, Andreas; Cherif, Chokri
A coreless manufacturing process for generic 3D rigid frame topologies will be introduced in this paper. The aim is to extend the field of filament winding from mainly 2D-shells and some exceptional cases of 3D rigid frames. This manufacturing process employs a coreless translation cross-winding method in order to continuously deposit a roving around deflection points in space. On this basis, a design methodology is being created and deductively verified by designing a beam for a three-point bending load case. The composite beam is designed on a macro level simulation approach to match the stiffness of a reference aluminum profile, which is commonly employed as structural component for robotic gripper systems in automotive assemblies. The performance of the beams is subsequently compared by three-point bending experiments. This demonstrates that the composite beam offers equivalent stiffness and strength properties with a weight-reduction potential of nearly 50% for bending loads.